UNDERSTANDING THE PSYCHOLOGICAL BARRIERS: INVESTIGATING EFL STUDENTS’ ANXIETY IN ACADEMIC WRITING - Rifka Rahmita; Lusi Nurhayati (Universitas Muhammadiyah Makassar, 2026)
Writing anxiety is a continual obstacle that can impede academic performance, writing quality, and language acquisition among students learning English as a foreign language; nevertheless, most research has concentrated on undergraduate populations or contexts outside of Indonesia. This study examines academic writing anxiety experienced by graduate EFL learners in Yogyakarta to address this gap. The aim was to investigate the levels, types, and causes of anxiety in academic writing through a descriptive quantitative methodology with 32 participants. Data were gathered utilizing the Second Language Writing Anxiety Inventory (SLWAI) and the Causes of Writing Anxiety Inventory (CWAI). The results reveal significant levels of writing anxiety (M = 74), with cognitive anxiety being the predominant type (M = 26.22), followed by somatic anxiety (M = 24.72) and avoidance behavior (M = 23.06). Regarding its causes, writing anxiety was primarily attributed to the fear of the lecturer’s negative comments, time pressure, and pressure for perfect work. These findings demonstrate that writing anxiety constitutes a significant barrier that may impede academic success and limit students’ ability to produce high-quality academic writing. This study offers empirical novelty by situating the investigation within a localized Indonesian graduate context, thereby extending the literature beyond commonly studied undergraduate populations. Furthermore, the findings contribute to pedagogical practices by emphasizing the importance of constructive feedback, effective time management, and a learning environment that supports continuous development in academic writing. In conclusion, targeted interventions are essential to reduce anxiety, strengthen students’ writing confidence, and enhance academic achievement and writing outcomes.